Acne: more than skin deep. Issue 970 (4th August 2006) - Ayer, J; Burrows, N
Abstract : Acne is one of the most prevalent skin conditions affecting teenagers. It is a disease of the pilosebaceous unit. Blockage of sebaceous glands and colonisation with Proionobacterium acnes leads to acne. Grading the severity of acne helps to determine the appropriate treatment. Treatment of acne should be started as early as possible to minimise the risk of scarring and adverse psychological effects. It should be tailored to the individual patient, the type of acne, its severity, the patient's ability to use the treatment, and the psychological state. Topical agents are the mainstay for treatment of mild acne. Moderate acne is treated with oral antibiotics. Resistance to antibiotics may be reduced by subsequent use of non-antibiotic topical medications. Severe acne is treated with isotretinoin, and this can lead to permanent remission. With better education and care given by medical profession, acne treatment could be significantly improved.